Australian graduates' work readiness – deficiencies, causes and potential solutions. Issue 2 (29th November 2019) - Prikshat, Verma; Montague, Alan; Connell, Julia; Burgess, John
Abstract : Purpose: It is widely reported that there is a competence deficit between graduating from Australian higher education (HE) and becoming work ready and that the deficit is becoming more pronounced. The purpose of this paper is to examine the work readiness competencies of Australian HE and vocational education (VE) graduates. The reported competence deficits, the causes of these deficits and the potential strategies to overcome these deficits are discussed. Design/methodology/approach: A qualitative, inductive research design was used to examine Australian graduates' work readiness competence, potential deficits, their causes and possible solutions to gain some preliminary insights and help shape future research. A multiple case design was used comprising key stakeholders' in-depth interviews and focus group discussions. In-depth semi-structured interviews and focus group discussions were conducted to gain insights from the key stakeholders. Findings: The stakeholders reported that the Australian VE and HE sectors do not sufficiently prepare graduates in terms of their work readiness skills. Self-management skills, communication (written and expression), team-work skills, cognitive skills, system thinking and innovation and creativity were the main work readiness competency deficits reported by the stakeholders. Research limitations/implications: The research has its limitations in terms of the limited sample and time frame, and the absence of input from graduates. The results of the study indicate the deteriorating state of the Australian graduate labour market and emphasise that an integrated approach is urgently required from all stakeholders to facilitate the transition and reduce the time taken from graduation to employment. Originality/value: The focus of the study is located in the Australian labour market in terms of the competencies that reportedly are present upon graduation and the competencies that employers are looking for on recruitment. The requisite competency list and the deficits are examined through the lens of four stakeholder groups; government representatives, industry representatives and VE and HE representatives.